Classical social theory in use : interpretation and application for educators and other non-specialists - Bickel, Robert (Emerald Publishing Limited : Information Age Publishing, Inc., 2013)
This book provides an introduction to classical social theory through discussion, application, and synthesis of the work of Karl Marx, Emile Durkheim, and George Herbert Mead. Rather than merely summarizing and evaluating their continuing influence, their ideas and ways of reasoning are applied in thoroughly developed fashion to contemporary issues and historical events of enduring importance. In the process, contributions of these three very different authors are used to complement each other and are eventually synthesized, making clear that they can be melded into one multilevel, even if tentative and rudimentary, theoretical perspective. The book is intended to systematically and compactly introduce the most useful concepts of the three classical theorists. However, new concepts are typically introduced as part of the narrative, rather than in box-text definitional fashion. This is consistent with the books primary purpose: to enable the reader to begin to think like Marx, Durkheim, and Mead, especially insofar as their work can be synthesized into one point of view, dealing with inter-related macro-level, middle range, and micro-level social phenomena. The section on Marx will be longer than the sections on Durkheim and Mead. In part, the length of the discussion of Marx's work is due to use of this section to begin introducing pertinent ideas of Durkheim and Mead.